PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI MCDONALDS CISAUK SURADITA - Wanda Septia Bachtiar; Suworo (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of service quality and location on purchasing decisions at McDonald's Cisauk Suradita both partially and simultaneously. The method used is quantitative method with descriptive approach. while obtaining data is done by distributing questionnaires to 100 respondents. The results of the research on service quality have a significant effect on purchasing decisions partially, as evidenced by the regression equation Y = 3.723 + 0.826 X1., the correlation coefficient of 0.767 means that the two variables have a strong relationship. The determination value is 0.588 or 58.8% while the remaining 41.2% is influenced by other factors. Hypothesis testing obtained tcount> ttable or (11.820> 1.984) This is also reinforced by the value of ρ value < Sig.0.05 or (0.000 <0.05). Location has a significant effect on purchasing decisions partially as evidenced by the results of the regression equation Y = 6.675 + 0.731X2, the correlation coefficient of 0.669 means that the two variables have a very strong level of relationship. The determination value is 0.447 or 44.7% while the remaining 52.3% is influenced by other factors. Hypothesis testing obtained tcount> ttable value or (8.905> 1.984) This is also reinforced by the ρ value < Sig.0.05 or (0.000 < 0.05)]. The results of research on service quality and location simultaneously have a significant effect on purchasing decisions as evidenced by the results of the regression equation Y = 0.227 + 0.633 X1 + 0.277 X2. The correlation coefficient between the independent variable and the dependent variable is obtained at 0.787, meaning that it has a strong relationship. The simultaneous coefficient of determination is 0.620 or 62% while the remaining 38% is influenced by other factors. Simultaneous hypothesis testing obtained Fcount> Ftabel or (79.034> 2.700) This is also reinforced by the ρ value < Sig.0.05 or (0.000 < 0.05). Thus H0 is rejected and H3 is accepted. This means that there can be a significant effect simultaneously between service quality and location on purchasing decision interest.